Long-Term Oxygen Therapy and Patient Education in Chronic Obstructive Pulmonary Disease - ERMİŞ, Zeliha (MAS Journal of Applied Sciences, 2023)
Chronic Obstructive Pulmonary Disease (COPD) constitutes a significant portion of chronic respiratory diseases. The economic and social burden of COPD, which is a preventable and treatable disease all over the world, is increasing and causing significant mortality and morbidity worldwide. Long-term oxygen therapy (LTOT) is the most widely used method in the treatment of acute and chronic respiratory failure in COPD. In long-term use of oxygen, serious risks may occur in patients if the application instructions are not followed. In order to cope with the psychological and physiological difficulties experienced by patients receiving LTOT and to protect them from possible risks, it is important for nurses to be informed about the effect of oxygen therapy, possible side effects and precautions to be taken, and to inform patients. In this article, it is aimed to give information about the purpose of oxygen therapy, complications and patient education in oxygen therapy in patients with COPD and LTOT.